Postlarval morphology of the Western White Shrimp Penaeus occidentalis (Crustacea: Pennaeidae) - Katani M., Hiroshi (1996)
The postlarval morphology of wild Penaeus occidentalis was described by Kitani (1994). but a comparison between wild and laboratory postlarvae was not available. This paper presents that comparison.